Hallmarks and Determinants of Oncogenic Translation Revealed by Ribosome Profiling in Models of Breast Cancer - Christos Vaklavas (Translational Oncology, 2020)
Gene expression is extensively and dynamically modulated at the level of translation. How cancer cells prioritize the translation of certain mRNAs over others from a pool of competing mRNAs remains an open question. Here, we analyze translation in cell line models of breast cancer and normal mammary tissue by ribosome profiling. We identify key recurrent themes of oncogenic translation: higher ribosome occupancy, greater variance of translational efficiencies, and preferential translation of transcriptional regulators and signaling proteins in malignant cells as compared with their nonmalignant counterpart. We survey for candidate RNA interacting proteins that could associate with the 5′untranslated regions of the transcripts preferentially translated in breast tumour cells. We identify SRSF1, a prototypic splicing factor, to have a pervasive direct and indirect impact on translation. In a representative estrogen receptor–positive and estrogen receptor–negative cell line, we find that protein synthesis relies heavily on SRSF1. SRSF1 is predominantly intranuclear. Under certain conditions, SRSF1 translocates from the nucleus to the cytoplasm where it associates with MYC and CDK1 mRNAs and upregulates their internal ribosome entry site–mediated translation. Our results point to a synergy between splicing and translation and unveil how certain RNA-binding proteins modulate the translational landscape in breast cancer.